CLIMATE VULNERABILITY ASSESSMENT OF SMALL AND LARGE SCALE PADDY FARMERS IN PALAKKAD DISTRICT, KERALA - SUMATHY M (The Journal of Research ANGRAU, 2026)
Palakkad has a total paddy area of 76503.68 hectare, of which the wet paddy area is 76361.21 hectare and total dry paddy area of 142.47 hectare. Weather, pest, disease, drought, and flood are the common natural or external risks. The external sources of risk cannot be controlled by farmers, which generally come from the natural environment. In this context, the study looks into the production risks pertaining from the external sources among the small and large scale farmers in the Palakkad district, Kerala. A vulnerability index is developed consisting of exposure, sensitivity and adaptive factors to understand the climate induced production risks among the selected sample farmers during 2005 to 2022.The data reveals that the exposure index is low (<= 11.96) for only minority of small farmers and most of themfell in high and very high category (more than 13.46). In the sensitivity category, majority of small and large farmers wereincluded in the high sensitivity index category group (11.45to 13.66).But the severities of these factors effecting them are different. Exposure factors had medium impact on large number of sample farmers, while, sensitivity factors create high impact on large number of farmers. Likewise, adaptive factors had high impact on small and large scale farmers. Even though adaptation practices are implemented in the district,more efforts were needed to implement them in a timely and systematic way.